Pengaruh Workplace Spirituality Terhadap Kinerja Organisasi: Systematic Literature Review - Anung Pramudyo; Edi Cahyono; Dwi Wahyu Pril Ranto; Sarjita Sarjita; Nunuk Dwi Garwanti Endang Palupi; Habib Ismail (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Using a methodical literature review technique, this study seeks to compile the most recent data about the impact of workplace spirituality on organizational performance. Using the keywords "job performance," "organizational performance," and "workplace spirituality," Google Scholar is the database that is used. Use the article search tool publish or perish to find English-language papers in the Google Scholar database between 2017 and 2025. 988 articles were found in the search results. Following the procedure for inclusion and exclusion, 40 suitable articles were found. The synthesis's findings demonstrate how organizational performance is impacted by workplace spirituality. According to this review, workplace spirituality can boost constructive employee behavior, which raises the caliber of work produced. Aside from that, workplace spirituality functions as a moderator and mediator in addition to being an independent variable. A concept map that illustrates the connection between workplace spirituality and different organizational outcomes is also created by this literature review. Additionally, this study is significant because it might serve as a reference for scholars wishing to delve further into the connection between job performance and workplace spirituality.